Why Plea Bargains Are Not Confessions - Garrett, Brandon L. (2016)
Is a plea bargain a type of confession? Plea bargaining is often justified as, at its core, a process involving in-court confession. The U.S. Supreme Court's early decisions approved plea bargains as something more than a confession which admits that the accused did various acts. I argue in this Article that plea bargains are not confessions-they do not even typically involve detailed admissions of guilt. The defendant generally admits to acts satisfying elements of the crime--a legally sufficient admission to be sure, but often not under oath, and often not supported by any extensive factual record. Because plea bargains typically contain only formulaic admissions, they have limited preclusive impact in future cases. The modern trend has been to find issues not precluded by a guilty plea, except perhaps as to elements of the charged offense. A deeper problem with the lack of adjudicated facts arises when other actors later seek to attach collateral consequences to the conviction. More careful development of the factual record could help to prevent at least some guilty pleas by innocent defendants, and additionally, that development could produce reforms that would more narrowly target the collateral consequences that now attach to entire categories of convictions. These benefits reveal that it is particularly important to understand precisely why plea bargains are not more than, and are in fact much less than, confessions